Liquid fiducial marker applicability in proton therapy of locally advanced lung cancer. Issue 3 (March 2017) - Scherman Rydhög, Jonas; Perrin, Rosalind; Jølck, Rasmus Irming; Gagnon-Moisan, Francis; Larsen, Klaus Richter; Clementsen, Paul; Riisgaard de Blanck, Steen; Fredberg Persson, Gitte; Weber, Damien Charles; Lomax, Tony; Andresen, Thomas Lars; Munck af Rosenschold, Per
Abstract: Background and purpose: We investigated the clinical applicability of a novel liquid fiducial marker (LFM) for image-guided pencil beam scanned (PBS) proton therapy (PBSPT) of locally advanced lung cancer (LALC). Materials and methods: The relative proton stopping power (RSP) of the LFM was calculated and measured. Dose perturbations of the LFM and three solid markers, in a phantom, were measured. PBSPT treatment planning on computer tomography scans of five patients with LALC with the LFM implanted was performed with 1–3 fields. Results: The RSP was experimentally determined to be 1.164 for the LFM. Phantom measurements revealed a maximum relative deviation in dose of 4.8% for the LFM in the spread-out Bragg Peak, compared to 12–67% for the solid markers. Using the experimentally determined RSP, the maximum proton range error introduced by the LFM is about 1 mm. If the marker was displaced at PBSPT, the maximum dosimetric error was limited to 2 percentage points for 3-field plans. Conclusion: The dose perturbations introduced by the LFM were considerably smaller than the solid markers investigated. The RSP of the fiducial marker should be corrected in the treatment planning system to avoid errors. The investigated LFM introduced clinically acceptable dose perturbations for image-guided PBSPT of LALC.